2018
DOI: 10.4055/cios.2018.10.4.500
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the EOS Imaging System for Assessment of the Spinal and Pelvic Alignment in the Sagittal Plane

Abstract: BackgroundThe sagittal alignment of the spine and pelvis is not only closely related to the overall posture of the body but also to the evaluation and treatment of spine disease. In the last few years, the EOS imaging system, a new low-dose radiation X-ray device, became available for sagittal alignment assessment. However, there has been little research on the reliability of EOS. The purpose of this study was to evaluate the intrarater and interrater reliability of EOS for the sagittal alignment assessment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…Although studies have shown the utility of the biplanar EOS system, e.g. it has been shown to reliably assess spinal and pelvic alignment in the sagittal plane [23], we are not aware of any study that has compared it with radiographs and/or DXA for the diagnosis of vertebral fractures in children. EOS has the advantages of high image quality, low radiation dose and rapid acquisition time.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have shown the utility of the biplanar EOS system, e.g. it has been shown to reliably assess spinal and pelvic alignment in the sagittal plane [23], we are not aware of any study that has compared it with radiographs and/or DXA for the diagnosis of vertebral fractures in children. EOS has the advantages of high image quality, low radiation dose and rapid acquisition time.…”
Section: Discussionmentioning
confidence: 99%
“…The independent t -test and the chi-square test were used to compare baseline demographics data between the two groups. Intra-observer reliability and inter-observer reliability were assessed by calculating the κ correlation coefficient (with 1.0 representing total agreement and 0 representing no agreement) [ 15 ]; κ coefficients interpretation was performed using the Landis and Koch criteria [ 16 ]. They defined a κ value of >0.8 as “almost perfect agreement”, between 0.6 and 0.8 as “substantial agreement”, between 0.4 and 0.6 as “moderate agreement”, between 0.2 and 0.4 as ”fair agreement”, and <0.2 as “slight agreement”.…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, the importance of cervical spinal balance in sagittal plane is emphasized, and many studies have been reported 1 7 . The global spinal sagittal balance is generally explained by the relationship between the plumb line from the second vertebral body and first sacral body 8 .…”
Section: Introductionmentioning
confidence: 99%